Increased Entorhinal–Prefrontal Theta Synchronization Parallels Decreased Entorhinal–Hippocampal Theta Synchronization during Learning and Consolidation of Associative Memory - Takehara-Nishiuchi, Kaori; Maal-Bared, Geith; Morrissey, Mark (Frontiers in Behavioral Neuroscience, 2012)
Memories are thought to be encoded as a distributed representation in the neocortex. The medial prefrontal cortex (mPFC) has been shown to support the expression of memories that initially depend on the hippocampus (HPC), yet the mechanisms by which the HPC and mPFC access the distributed representations in the neocortex are unknown. By measuring phase synchronization of local field potential (LFP) oscillations, we found that learning initiated changes in neuronal communication of the HPC and mPFC with the lateral entorhinal cortex (LEC), an area that is connected with many other neocortical regions. LFPs were recorded simultaneously from the three brain regions while rats formed an association between an auditory stimulus (CS) and eyelid stimulation (US) in a trace eyeblink conditioning paradigm, as well as during retention one month following learning. Over the course of learning, theta oscillations in the LEC and mPFC became strongly synchronized following the presentation of the CS on trials in which rats exhibited a conditioned response (CR), and this strengthened synchronization was also observed during retention one month after learning. In contrast, CS-evoked theta synchronization between the LEC and HPC decreased with learning. Our results suggest that the communication between the LEC and mPFC is strengthened with learning whereas the communication between the LEC and HPC is concomitantly weakened, suggesting that enhanced LEC-mPFC communication may be a key process for theoretically-proposed neocortical reorganization accompanying encoding and consolidation of a memory.